2021
DOI: 10.3389/fneur.2021.686253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Novel Thrombectomy Device in Patients With Acute Ischemic Stroke: A Randomized Controlled Trial

Abstract: Purpose: The Tonbridge stent is a novel retriever with several design improvements which aim to achieve promising flow reperfusion in the treatment of acute ischemic stroke (AIS). We conducted a randomized controlled, multicenter, non-inferiority trial to compare the safety and efficacy of the Tonbridge stent with the Solitaire FR.Methods: AIS patients aged 18–85 years with large vessel occlusion in anterior circulation who could undergo puncture within 6 h of symptom onset were included. Randomization was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 3 It has been reported that ischemic stroke (IS) constitutes about 85% of all stroke patients. 4 Even though many efforts are being put into developing new strategies to treat ischemic stroke, the only effective treatment for stroke is intravascular thrombolysis or thrombectomy. 5 Thus, to identify novel therapies seems curial, and further to reveal the mechanism of the pathological progress in stroke would provide efforts to develop the new treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 3 It has been reported that ischemic stroke (IS) constitutes about 85% of all stroke patients. 4 Even though many efforts are being put into developing new strategies to treat ischemic stroke, the only effective treatment for stroke is intravascular thrombolysis or thrombectomy. 5 Thus, to identify novel therapies seems curial, and further to reveal the mechanism of the pathological progress in stroke would provide efforts to develop the new treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized clinical trial found no significant difference in infarct size between NBP and placebo groups in humans, although the NBP group exhibited better functional outcomes after 90 days poststroke. 21 Oral NBP treatment starting at 2 hours and for 3 weeks after ischemia/reperfusion also did not reduce infarct size in rhesus monkeys, although a trend of decreased infarct size was observed in the NBP group. 26 In our study, NBP starting at 6 hours and for 12 weeks also did not decrease infarct size at 4 weeks after permanent MCAO in cynomolgus monkeys, although it significantly improved WM.…”
Section: Discussionmentioning
confidence: 82%
“…The dosing regimen of NBP was established based on the standard clinical administration, involving a 14-day intravenous administration of 50 mg/day, followed by an oral regimen of 600 mg/day from day 15 to 90. 21 To adapt this dosage for use in cynomolgus monkeys, we used a dose translation method as follows: 22…”
Section: Methodsmentioning
confidence: 99%
“…The Tonbridge stent (Tonbridge Medical Technology, Guangzhou, China) was compared to the Solitaire stent-retriever in 208 patients with AIS due to LVO within 6 hours of symptom onset. The Tonbridge device showed non-inferiority, with similar rates of all-cause mortality and 90-day mRS of 0-2 [ 22 ].…”
Section: Reviewmentioning
confidence: 99%